THE UNIVERSITY OF TODAY: FROM THE MODEL TO THE RUSSIAN REALITY - A. V. Shchepilova; V. A. Goncharova; S. V. Mikhailova; A. E. Bazhanov; V. V. Alpatov (Высшее образование в России)
The article sheds light on the pivotal ideas of the present-day Russian system of higher education as a result of integration into the global system. Upon the analysis of several American and European universities it is possible to define the universal model of the successful modern university in terms of organization of academic process, scientific research and information system. Within the model defined the article presents the in-depth analysis of the Russian university as to it problems and potential. The analysis thus provides grounds to formulate the system principles of how higher education functions as well to state the necessity to reconsider the developmental strategy of higher education in Russia within the system approach and bearing in mind its unique historical and cultural identity.